Optimisasi Jumlah Produksi dalam Memperoleh Keuntungan Maksimal Pada Penjualan Dompet dan Tas Jimshoney â€œNAYA Online Shoppingâ€ - Umar, Rochmat (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2020)
ABSTRACT Linear programming is one of the most widely used operational research techniques in practice and is known for being easy to understand. The method in solving linear programming in